Unfortunately yours : [large type] a novel - Bailey, Tessa ([Vine mess], 2023)
"After losing her job and her fiancé in one fell swoop, Natalie Vos returned home to lick her wounds. A few months later, she's ready to get back on her feet, but she needs her trust fund to finance her new business venture. Unfortunately, the terms require she marry before she can have the money. August Cates is determined to do his late best friend proud running his vineyard, but he doesn't know jack about making wine. His tasting room is empty, his wine is disgusting (seriously, he once saw someone gag), and his buddy's legacy is circling the drain. No bank will give him the loan he needs to turn the business around . . . and then the gorgeous, feisty heiress knocks on his door. Natalie has haunted August's dreams since the moment they met, but their sizzling chemistry immediately morphed into simmering insults. Now, a sham marriage and a few weeks living under the same roof could help them both. Then they can go their separate ways - assuming they make it out alive. "--